Teaching reform of bilingual digital design technology in environmental design - Liu, Nianzu (Frontiers in Education, 2025)
Digital design technology is a compulsory course offered by the School of Design, Art and Architecture of Zhejiang Wanli University since 2020. The course was applied for a bilingual course construction project in 2022. This article summarizes the changes in software used in the graduation projects of our school’s environmental design major over the past two decades, the selection of design styles, and the relationship between them. From the selection of teaching content and the setting of student evaluation standards, this article proposes countermeasures and suggestions on how to introduce bilingual mode in teaching, attach importance to creative thinking training, multi-scenario teaching design and personalized education.